Measuring the effects of stormwater mitigation on beach attendance - Atiyah, Perla (2013)
Many studies have used valuation techniques to predict the potential effect of environmental improvements on human use of coastal areas, but there is a lack of post hoc empirical evidence that these policies indeed affect the way people use coastal areas. A panel data approach is developed to statistically determine how storm drain diversions affected attendance at 26 beaches in Southern California. This study uses a 10-year time series of data to conduct a statistical analysis of attendance at beaches with and without diversions and before and after the diversions were installed, while controlling for all observable, confounding factors. Results indicate that beach attendance increased at beaches with diversions compared to those that did not have diversions (between 350,000 and 860,000 visits annually at a 95% confidence interval). Establishing this link between mitigation policies and human use patterns can lead to better management of coastal areas.